The oil palm metallothionein promoter contains a novel AGTTAGG motif conferring its fruit-specific expression and is inducible by abiotic factors - Omidvar, Vahid; Abdullah, Siti Nor Akmar; Izadfard, Amir; Chai, Ling Ho; Mahmood, Maziah (Springer, 2010)
The 1,053-bp promoter of the oil palm metallothionein gene (so-called MSP1) and its 5′ deletions were fused to the GUS reporter gene, and analysed in transiently transformed oil palm tissues. The full length promoter showed sevenfold higher activity in the mesocarp than in leaves and 1.5-fold more activity than the CaMV35S promoter in the mesocarp. The 1,053-bp region containing the 5′ untranslated region (UTR) gave the highest activity in the mesocarp, while the 148-bp region was required for minimal promoter activity. Two positive regulatory regions were identified at nucleotides (nt) −953 to −619 and −420 to −256 regions. Fine-tune deletion of the −619 to −420 nt region led to the identification of a 21-bp negative regulatory sequence in the −598 to −577 nt region, which is involved in mesocarp-specific expression. Gel mobility shift assay revealed a strong interaction of the leaf nuclear extract with the 21-bp region. An AGTTAGG core-sequence within this region was identified as a novel negative regulatory element controlling fruit-specificity of the MSP1 promoter. Abscisic acid (ABA) and copper (Cu2+) induced the activity of the promoter and its 5′ deletions more effectively than methyl jasmonate (MeJa) and ethylene. In the mesocarp, the full length promoter showed stronger inducibility in response to ABA and Cu2+ than its 5′ deletions, while in leaves, the −420 nt fragment was the most inducible by ABA and Cu2+. These results suggest that the MSP1 promoter and its regulatory regions are potentially useful for engineering fruit-specific and inducible gene expression in oil palm.